2020
DOI: 10.1021/acs.est.0c03021
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Environmental Contaminants and Gastrointestinal Parasites: Novel Insights from an Integrative Approach in a Marine Predator

Abstract: Environmental contaminants and parasites are ubiquitous stressors that can affect animal physiology and derive from similar dietary sources (co-exposure). To unravel their interactions in wildlife, it is thus essential to quantify their concurring drivers. Here, the relationship between blood contaminant residues (11 trace elements and 17 perfluoroalkyl substances) and nonlethally quantified gastrointestinal parasite loads was tested while accounting for intrinsic (sex, age, and mass) and extrinsic factors (tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 82 publications
2
28
0
Order By: Relevance
“…HFB is highly sensitive to changes in oxygen tension in vivo and can be used as a valuable 19 F tracer to study the dynamic relationship between tumor vascular oxygenation and tissue oxygen tension [45] . PFN has been reported to be a well‐tolerated and stable oral fluorinated reagent for gastrointestinal imaging in vivo [46] …”
Section: F Mri Contrast Agentsmentioning
confidence: 99%
“…HFB is highly sensitive to changes in oxygen tension in vivo and can be used as a valuable 19 F tracer to study the dynamic relationship between tumor vascular oxygenation and tissue oxygen tension [45] . PFN has been reported to be a well‐tolerated and stable oral fluorinated reagent for gastrointestinal imaging in vivo [46] …”
Section: F Mri Contrast Agentsmentioning
confidence: 99%
“…Despite restrictions, LC-PFAAs remain ubiquitous and are still found in high concentrations in wildlife (Custer et al 2019;Sedlak et al 2017;Sun et al 2019) and humans (Calafat et al 2007;Song et al 2018), while the intrinsic (sex, age, body condition) and extrinsic (food resources ) factors that determine wildlife exposure are not yet well understood (Kannan 2011;Land et al 2018;Prevedourus et al 2006;Carravieri et al 2020), especially in highly contaminated areas where the exposure profile is different from that found in remote areas (Armitage et al 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, contradictory results have been reported when the relationship between PFAA compounds, age and condition of wildlife was investigated. Although some PFAAs compounds are known to be bioaccumulative (Haükas et al 2007), there is no clear pattern how PFAA concentrations increase with age (Bustnes et al 2013;Carravieri et al 2020;Dauwe et al 2006;Holmstrom and Berger 2008;Loseth et al 2019;Route et al 2014). Regarding condition, studies have found negative (Barghi et al 2018;Van den Vijver et al 2004), positive (Barghi et al 2018;Tartu et al 2014) or no associations (Hoff et al 2005;Svendsen et al 2018;Tartu et al 2017) between several PFAA compounds and body condition.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the latitudinal δ 13 C isoscapes available for marine predators in the Southern Ocean (Cherel and Hobson 2007;Jaeger et al 2010), the positive correlation between Hg concentrations and δ 13 C values tends to confirm that species foraging in cold sub-Antarctic waters were less prone to contamination than species foraging in warmer subtropical waters. Despite the poleward increase in surface waters Hg concentrations (Cossa et al 2011), previous investigations considering a larger latitudinal range from the Antarctic to the subtropics found the same contamination pattern (Blévin et al 2013;Carravieri et al 2017Carravieri et al , 2020b, which was attributed to the higher complexity of food webs at lower latitudes (Carravieri et al 2014b).…”
Section: Influence Of Feeding Habitats On Hg Concentrationsmentioning
confidence: 76%
“…When compared with bulk isotopic analysis, the 2 main interests of the approaches are: 1) the quantification of both baseline and trophic δ 15 N values on the same consumer tissue sample, and 2) the relative estimation of trophic position of consumers by subtracting baseline to trophic δ 15 N values. Despite the great advantages of this technique, few studies have yet used it to study the influence of foraging ecology on Hg concentrations in seabirds (Elliott and Elliott 2016; Gagné et al 2019; Carravieri et al 2020b).…”
Section: Methodsmentioning
confidence: 99%